Changes in Interhemispheric Motor Connectivity Across the Lifespan: A Combined TMS and DTI Study - Strauss, Sebastian; Lotze, Martin; Flöel, Agnes; Domin, Martin; Grothe, Matthias (Frontiers in Aging Neuroscience, 2019)
Age-related decline in interhemispheric connectivity between motor areas has been reported with both transcranial magnetic stimulation (TMS) and diffusion tensor imaging (DTI) measurements. However, not all studies were able to confirm these findings, and previous studies did not apply structural (DTI) and functional (TMS) measurements within each individual appropriately. Here we investigated age dependency of the ipsilateral silent period (ISP) and integrity of fibers in the corpus callosum as operationalized by fractional anisotrophy (FA), using TMS and DTI, respectively, in 20 participants between 19 and 72 years of age. We found age-dependent increase for ISP, and decrease of FA, both indicating a decrease in interhemispheric inhibition, with a strong negative association between FA and ISP for the dominant hemisphere (r=-0.39, p=0.043). Our findings suggest that aging leads to decline of interhemispheric motor connectivity, as evidenced in both structural and functional parameters, which should be taken into account when interpreting disease-or medication-related changes.